Safety of zidovudine dose reduction in treatment‐naïve HIV infected patients. A randomized controlled study (MiniZID). Issue 3 (10th September 2015) - Rougemont, M; Nchotu Ngang, P; Stoll, B; Delhumeau, C; Hill, A; Ciaffi, L; Bonnet, F; Menga, G; Fampou, J‐C; Calmy, A
Abstract : Background: Since September 2014, zidovudine (ZDV)‐based therapy for HIV has been the preferred second‐line WHO regimen in Cameroon, but its use is limited by the risk of anaemia at standard dosage. We assessed the safety of a reduced vs . standard dose of ZDV to decrease the risk of anaemia in treatment‐naïve, HIV‐infected individuals. Methods: In a prospective, randomized, open‐label trial in an HIV clinic in Cameroon, 142 eligible adults (CD4 count < 350 cells/μL) were randomized to receive 24 weeks of a regimen comprising lamivudine plus nevirapine with either a reduced (400 mg) or standard dose (600 mg) of ZDV. The primary endpoint was the proportion of participants with new/worsening anaemia. Results: Median age was 35 years; 58.5% were women; median body mass index was 23.2 kg/m 2 . At baseline, median haemoglobin was 11.6 g/dL, median CD4 cell count was 163 cells/μL, and median plasma HIV‐1 RNA load was 5.4 log10 copies/mL. The proportion of participants with new/worsening anaemia was 37.5% (400 mg ZDV) and 32.9% (600 mg ZDV) ( P = 0.563). Ten patients with severe anaemia required a switch from ZDV to tenofovir (11.4% in standard‐dose arm vs . 2.8% in low‐dose arm; P = 0.054). At 24 weeks, there was no significant difference between treatment groups, including median CD4 T‐cell count increases. Conclusions: No significant difference was observed in the overall rate of anaemia between HIV‐infected individuals starting a ZDV‐based treatment according to a standard‐ or reduced‐dose regimen. Severe anaemia and treatment switches related to study drug, however, were more frequent with 600 mg than 400 mg ZDV.